DETERMINAN KERUSAKAN LINGKUNGAN DI NEGARA ORGANISASI KERJASAMA ISLAM (OKI) (STUDI ENVIRONMENTAL KUZNETS CURVE) - Socalina, Erlin (Universitas Negeri Yogyakarta, 2024)
Globalization that continues to grow massively every year, can be felt globally and regionally. This study is intended to determine the effect of economic growth, population, and industrial production on environmental damage using the EKC study in the Organization of Islamic Cooperation (OIC). Uses quantitative research methods with the E-views 9 analysis tool. This study uses panel data regression analysis with Fixed Effect Model (FEM) as the best model analysis. The results of statistical tests show that variable economic growth can have an influence on environmental damage with the EKC study. Then the population variable shows direction towards environmental damage and industrial production has an influence on environmental damage with the EKC study in the Organization of Islamic Cooperation (OIC).